Implementing Burundi's national e-health enterprise architecture: past, present and future - Verbeke, Frank; Kaze, Sandrine; Ajeneza, Larissa; Nkurunziza, Lambert; Sindatuma, Gervais; Hassan, Asmini; Van Bastelaere, Stefaan; Mugisho, Etienne (Journal of Health Informatics in Africa, 2017)
Background and purpose: The Ministry of Health (MoH) of Burundi initiated in 2014 the development of a national e-health enterprise architecture aiming to reclaim its leadership in this field and to better align existing and future ICT implementations in the health domain with the strategic options defined by the National Plan for Health Development (PNDS). Methods: The Open Group Architecture Framework (TOGAF) was used as a method for developing Burundi’s e-health enterprise architecture. A first part of the study consisted of a detailed analysis of regulatory documents and strategic plans related to the Burundian health system and health informatics development. In a second part, field visits and semi-structured interviews were organized with a representative sample of relevant health structures throughout the country. Thorough analysis of human resources, business processes, hardware, software, communication and networking infrastructure provided both a baseline and a target e-health situation. Finally, a strategic document was developed for planning the way forward for filling the functional and technical gaps that had been identified.Results: the preliminary study demonstrated the donor driven unequal distribution of hardware equipment over health administration components and health facilities. Internet connectivity was problematic and few health oriented business applications had found their way to the Burundian health system. Paper based instruments remained predominant in Burundi’s health administration. The study also identified a series of problems introduced by the uncoordinated development of health ICT in Burundi such as the lack of standardization, data security risks, varying data quality, inadequate ICT infrastructures, an unregulated e-health sector and insufficient human capacity. The later architecture development effort resulted in the production and validation of a national e-health strategy for Burundi for the period 2015-2019 (PNDIS). This strategy has been put into implementation by the Ministry of Public Health and Fight against Aids since 2015 with the help of the country’s development partners.Conclusions: the results demonstrated the challenging situation of the Burundian health information system but also revealed a series of important opportunities for the future: a political will to reclaim MoH leadership in the health information management domain based on the PNDIS, the readiness to develop e-health education and training programs and the opportunity to capitalize the experiences with DHIS2 deployment, results based financing monitoring and evaluation with OpenRBF and hospital information management systems implementation based on OpenClinic GA.Keywordse-Health enterprise architecture, TOGAF, Health information systems, Burundi